Art as activation: Mars on Nuns Island, Galway - Patrick Collins (Societal Impacts)
As part of the Galway International Arts Festival 2022, we invited British artist Luke Jerram to install his work, Mars, at a long vacant building close to the city centre of Galway, Ireland. This paper examines how an artistic installation transformed a forgotten place into a site for engagement, reflection, and dialogue about the city’s future. The paper traces the impact of inviting the public to experience their surroundings differently, challenging perceptions of space, history, and possibility. By disrupting the routine use of the urban environment, we can generate discourse on culture, participation, and civic responsibility. Giving people a voice in the future of place development is needed in an Ireland that is one of Europe’s most centralised and where the vagaries of property speculation has had serious economic and social consequences in the recent past.